Perovskite solar cell and preparation method thereof

By introducing an interface modification layer and an organic light absorption layer made of ionic liquid including methylamine functional groups into perovskite solar cells, the problem of the structural defects of perovskite solar cells affecting the photoelectric conversion efficiency is solved, and the effect of improving device stability and photoelectric conversion efficiency is achieved.

CN119653975APending Publication Date: 2025-03-18JITRI INST OF ORGANIC OPTOELECTRONICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411777882.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The photoelectric conversion efficiency of existing perovskite solar cells is affected by material structural defects, and the existing modification methods are not ideal.

Method used

In the perovskite solar cell, an interface modification layer made of an ionic liquid including methylamine functional groups is introduced, located between the electron transport layer and the perovskite light absorbing layer, and at least one connecting layer and an organic light absorbing layer are provided between the perovskite light absorbing layer and the hole transporting layer.

Benefits of technology

Through the introduction of the interface modification layer, the defects of perovskite materials are effectively suppressed, carrier transmission is optimized, and device stability and photoelectric conversion efficiency are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119653975A_ABST
    Figure CN119653975A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solar cells, in particular to a perovskite solar cell and a preparation method thereof. The perovskite solar cell comprises a bottom electrode, an electron transport layer, a perovskite light absorption layer, a hole transport layer and a top electrode which are sequentially arranged from bottom to top, wherein an interface modification layer is also arranged between the electron transport layer and the perovskite light absorption layer, and the interface modification layer is prepared from an ionic liquid containing a methylamine functional group. According to the perovskite solar cell provided by the invention, the structural defects of the perovskite solar cell are effectively suppressed, carrier transport is optimized, and the stability and photoelectric conversion efficiency of a device are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of solar cells, and in particular to a perovskite solar cell and a preparation method thereof. Background Art

[0002] Among many emerging energy sources, solar energy is an unlimited and widely distributed natural resource. Its unique advantages make it increasingly prominent in the process of global energy transformation. Perovskite solar cells are widely cited due to their amazing efficiency growth rate, significant cost advantages and easy large-scale production.

[0003] However, since the structural defects of the perovskite material itself will affect its photoelectric conversion efficiency, the existing technology often modifies the exposed surface of the perovskite solar cell to reduce the impact of the structural defects of the perovskite material on the photoelectric conversion efficiency. However, this method of only modifying the exposed surface of the perovskite solar cell is not ideal for improving the photoelectric conversion efficiency. Summary of the invention

[0004] In order to solve the deficiencies of the prior art, the purpose of the present application is to provide a perovskite solar cell to suppress the defects of the perovskite material and improve the photoelectric conversion efficiency.

[0005] To achieve the above-mentioned purpose, the present application provides a perovskite solar cell, comprising a bottom electrode, an electron transport layer, a perovskite light absorption layer, a hole transport layer and a top electrode arranged in sequence from bottom to top; wherein an interface modification layer is also arranged between the electron transport layer and the perovskite light absorption layer, and the interface modification layer is prepared from an ionic liquid including a methylamine functional group.

[0006] Furthermore, at least one connecting layer and an organic light absorbing layer are sequentially stacked between the perovskite light absorbing layer and the hole transport layer.

[0007] To achieve the above objectives, the present application provides a method for preparing a perovskite solar cell, comprising:

[0008] preparing a bottom electrode;

[0009] preparing an electron transport layer on the bottom electrode;

[0010] preparing an interface modification layer on the electron transport layer using an ionic liquid including a methylamine functional group;

[0011] preparing a perovskite light absorbing layer on the interface modification layer;

[0012] preparing a hole transport layer on the perovskite light absorbing layer;

[0013] A metal electrode is prepared on the hole transport layer.

[0014] Furthermore, the method further comprises:

[0015] preparing a connecting layer on the perovskite light absorbing layer;

[0016] An organic light absorbing layer is prepared on the connecting layer.

[0017] Furthermore, the specific steps of preparing the interface modification layer using the ionic liquid including the methylamine functional group on the electron transport layer include:

[0018] A mixed solution of methylammonium propionate ionic liquid and dimethyl sulfoxide is spin-coated on the electron transport layer to prepare an interface modification layer, wherein the concentration of the methylammonium propionate ionic liquid in the mixed solution of methylammonium propionate ionic liquid and dimethyl sulfoxide is 0.01 mmol / mL-1 mmol / mL.

[0019] Furthermore, the specific steps of preparing the electron transport layer on the bottom electrode include:

[0020] Zinc oxide and isopropyl alcohol are mixed evenly in a volume ratio of 1:3-1:10 and then spin-coated on the bottom electrode to form a zinc oxide layer. After the spin coating is completed, a solution of tin oxide and pure water is mixed evenly in a volume ratio of 1:6.5 and then spin-coated on the zinc oxide layer;

[0021] After thermal annealing, an electron transport layer is obtained.

[0022] Furthermore, the specific steps of preparing the perovskite light absorption layer on the interface modification layer include:

[0023] Dissolving cesium iodide, lead iodide and cesium bromide in a mixed solvent of DMSO and anhydrous ethanol to obtain a perovskite solution;

[0024] Spin coating the perovskite solution onto the interface modification layer;

[0025] After annealing using a two-step annealing method, the perovskite light absorption layer is obtained.

[0026] Furthermore, the specific steps of preparing a connection layer on the perovskite light absorbing layer include:

[0027] The polythiophene donor (PDCBT) was dissolved in chlorobenzene (CB) at a concentration of 4 mg / mL and spin-coated onto the perovskite light absorption layer at a speed of 1500 rpm / min for 35 s, and annealed at 85 °C for 1 min.

[0028] Molybdenum trioxide and gold were deposited by thermal evaporation, and then ZnO and isopropyl alcohol (IPA) were evenly mixed in a ratio of 1:7 by spin coating. The speed was set to 3000 rpm / min for 30 s, and annealed at 90°C after spin coating.

[0029] BCP was deposited by thermal evaporation to obtain a connecting layer.

[0030] Furthermore, the specific steps of preparing a hole transport layer on the perovskite light absorption layer include:

[0031] The polythiophene donor was dissolved in chlorobenzene at a concentration of 4 mg / mL and spin-coated onto the perovskite light absorption layer. The rotation speed was set to 1500 rpm / min for 35 s, and then annealed at 85°C for 1 min. Molybdenum trioxide was then deposited by thermal evaporation to obtain a hole transport layer.

[0032] To achieve the above objectives, the present application also provides a perovskite solar cell, which is prepared using the perovskite solar cell preparation method as described above.

[0033] A perovskite solar cell of the present application effectively suppresses the structural defects of the perovskite solar cell, optimizes carrier transport, and improves the stability and photoelectric conversion efficiency of the device by configuring an interface modification layer composed of an ionic liquid including a methylamine functional group.

[0034] Other features and advantages of the present application will be set forth in the following description, and in part will become apparent from the description, or may be understood by practicing the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The accompanying drawings are used to provide a further understanding of the present application and constitute a part of the specification. Together with the embodiments of the present application, they are used to explain the present application and do not constitute a limitation of the present application. In the accompanying drawings:

[0036] Figure 1 This is a schematic diagram of the structure of the perovskite solar cell according to Example 1 of the present application;

[0037] Figure 2 This is a schematic diagram of stability comparison of the perovskite solar cell of Example 1 of the present application;

[0038] Figure 3 This is a schematic diagram of the structure of a perovskite solar cell according to Example 2 of the present application;

[0039] Figure 4 Schematic diagram of the IV curve of the perovskite solar cell of Example 2 of the present application;

[0040] Figure 5This is a schematic diagram of a process for preparing a perovskite solar cell according to Example 3 of the present application;

[0041] Figure 6 The device efficiency IV curves of perovskite solar cells prepared with different concentrations of MAPA;

[0042] Figure 7 The device efficiency comparison diagram of perovskite solar cells prepared with different concentrations of MAPA;

[0043] Figure 8 This is a schematic diagram of the process of preparing a perovskite solar cell according to Example 4 of the present application. DETAILED DESCRIPTION

[0044] The embodiments of the present application will be described in more detail below with reference to the accompanying drawings. Although certain embodiments of the present application are shown in the accompanying drawings, it should be understood that the present application can be implemented in various forms and should not be construed as being limited to the embodiments described herein. Instead, these embodiments are provided to provide a more thorough and complete understanding of the present application. It should be understood that the drawings and embodiments of the present application are only for exemplary purposes and are not intended to limit the scope of protection of the present application.

[0045] It should be understood that the various steps described in the method implementation of the present application can be performed in different orders and / or performed in parallel. In addition, the method implementation may include additional steps and / or omit the steps shown. The scope of the present application is not limited in this respect.

[0046] The term "including" and its variations used herein are open inclusions, i.e., "including but not limited to". The term "based on" means "based at least in part on". The term "one embodiment" means "at least one embodiment"; the term "another embodiment" means "at least one additional embodiment"; the term "some embodiments" means "at least some embodiments". The relevant definitions of other terms will be given in the following description.

[0047] It should be noted that the modifications of "one" and "plurality" mentioned in this application are illustrative rather than restrictive, and those skilled in the art should understand that unless otherwise clearly indicated in the context, it should be understood as "one or more". "Plurality" should be understood as two or more.

[0048] Hereinafter, embodiments of the present application will be described in detail with reference to the accompanying drawings.

[0049] Example 1

[0050] An embodiment of the present application provides a perovskite solar cell, referring to Figure 1 , including the following from bottom to top:

[0051] A bottom electrode 100 , an electron transport layer 200 , an interface modification layer 300 , a perovskite light absorption layer 400 , a hole transport layer 700 and a top electrode 800 .

[0052] In this embodiment, the bottom electrode is an ITO transparent conductive electrode.

[0053] In some other embodiments, the bottom electrode 100 may also be made of materials such as FTO electrode and AZO electrode.

[0054] In this embodiment, the electron transport layer 200 is composed of a tin oxide (SnO 2 ) layer 202 and a zinc oxide (ZnO) layer 201 stacked one above the other.

[0055] In this embodiment, the interface modification layer 300 is prepared from methylamine propionate (MAPA) ionic liquid and dimethyl sulfoxide (DMSO).

[0056] In some other embodiments, methylamine propionate (MAPA) may also be replaced by ionic materials containing methylamine functional groups such as methylamine formate and methylamine acetate.

[0057] In this embodiment, the perovskite light absorbing layer 400 is CsPbI 2.2 Br 0.8 .

[0058] In some other embodiments, the perovskite light absorbing layer may also be Any one of .

[0059] In this embodiment, the interface modification layer 300 has an interface modification effect on a series of perovskite light absorption layers such as mixed halogen and mixed cation.

[0060] In this embodiment, the hole transport layer 700 includes a polythiophene donor (PDCBT) layer 701 and a molybdenum trioxide MoO 3 layer 702 disposed on the polythiophene donor (PDCBT) layer 701 .

[0061] In this embodiment, the top electrode 800 is made of Ag.

[0062] In some other embodiments, the top electrode 800 may also be any one of a Cu electrode, an Au electrode, and a C electrode.

[0063] Figure 2 Schematic diagram of stability comparison of the perovskite solar cell of Example 1 of the present application, as shown in Figure 2 As shown, the red line represents the target, which represents the perovskite solar cell of Example 1 of the present application, and the black line represents the control, which represents the stacked cell without the interface modification layer. Figure 2It can be seen that, compared with the control device, the efficiency of the battery in Example 2 of the present application changes with time, and the efficiency does not drop significantly within 40 days, and the battery efficiency has good stability.

[0064] The perovskite solar cell of the embodiment of the present application was tested and the device efficiency was determined to be 18.29%, the open circuit voltage was 1.33V, the fill factor was 80.39, and the short circuit current density was 17.15mA / cm 2 A. It was found that MAPA can - Ions and lead Pb 2+ The interaction of ions suppresses the Pb-Pb dimer defects in the perovskite, thereby improving the morphology of the perovskite film and optimizing the crystallization properties of the perovskite film, thereby improving the device efficiency and stability.

[0065] Example 2

[0066] An embodiment of the present application provides a perovskite solar cell, referring to Figure 3 The difference between the perovskite solar cell of the present embodiment and the embodiment 1 is that:

[0067] The perovskite solar cell of Example 2 of the present application is a stacked cell, and an organic light absorption layer 600 is further provided on the perovskite light absorption layer via a connection layer 500 .

[0068] In some other embodiments, multiple layers of organic light absorbing layers may be provided by providing multiple layers of connecting layers.

[0069] In this embodiment, the connection layer 500 includes a polythiophene donor (PDCBT) layer 501, a molybdenum trioxide layer 502, a gold layer 503, a zinc oxide layer 504 and a BCP layer stacked from bottom to top.

[0070] In some other embodiments, the connection layer 500 may also be any structure that can connect to the perovskite light absorbing layer.

[0071] In this embodiment, the organic light absorbing layer 600 is made of PM6:mbzs-4f.

[0072] It should be noted that mbzs-4f is a non-fullerene small molecule.

[0073] In some other embodiments, the organic light absorbing layer 600 may also be prepared from PM6:CH1007, PM6:Y6:PC71BM, PM6:Y6, etc.

[0074] It can be understood that the Chinese name of CH1007 is: 2,2'-(((2Z,2'Z)-((12,13-bis(2-butyloctyl)-3,9-henedecyl-12,13-dihydroselenobenzo[2",3":4',5']thieno[2',3':4,5]pyrrolo[3,2-G]selenophene; the Chinese name of Y6 is Y6; the Chinese name of PC71BM is [6,6]-phenyl-C71-butyric acid methyl ester.

[0075] It should be noted that, in this embodiment, the hole transport layer 700 is only a MoO3 layer.

[0076] It should be noted that the chemical formula of PM6 is (C68H76F2O2S8)n, and its Chinese name is: poly[(2,6-(4,8-bis(5-(2-ethylhexyl-3-fluoro)thiophene-2-yl)-benzo[1,2-B:4,5-B']dithiophene])-ALT-(5,5-(1',3'-di-2-thiophene-5',7'-bis(2-ethylhexyl)benzo[1',2'-C:4',5'-C']dithiophene-4,8-dione);

[0077] It should be noted that the Chinese name of BCP is: 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline.

[0078] Figure 4 Schematic diagram of the IV curve of the perovskite solar cell of Example 2 of the present application, where the open circuit voltage (V OC ) is 2.09V, the short-circuit current (J SC ) is 14.55mA / cm 2 , the fill factor (FF) is 76.34% and the photoelectric conversion efficiency (PCE) is 23.19%.

[0079] Example 3

[0080] One embodiment of the present application provides a method for preparing a perovskite solar cell, referring to Figure 5 ,include:

[0081] Step S101: preparing a bottom electrode.

[0082] Specifically, the indium tin oxide (ITO) substrate was cleaned with pure water, acetone and anhydrous ethanol in sequence, then placed in a drying oven for drying, and then ozone was generated with an ozone machine for 15 minutes to obtain a bottom electrode.

[0083] Step S102: preparing an electron transport layer on the bottom electrode.

[0084] Specifically, zinc oxide ZnO and isopropyl alcohol IPA are evenly mixed in a volume ratio of 1:7 and then spin-coated on the ITO substrate after ozone, i.e., the bottom electrode, and the rotation speed is set to 3000 rpm / min for 30 seconds. After the spin coating is completed, tin oxide (SnO2) and pure water are evenly mixed in a ratio of 1:6.5, and the solution is spin-coated on the zinc oxide (ZnO) layer. The rotation speed is set to 3000 rpm / min for 30 seconds. After the spin coating is completed, it is placed on a hot stage at 150°C for annealing for 10 minutes to obtain an electron transport layer.

[0085] In some other embodiments, zinc oxide ZnO and isopropyl alcohol IPA are uniformly mixed in a volume ratio of 1:3-1:10.

[0086] Step S103: preparing an interface modification layer on the electron transport layer using a MAPA ionic liquid solution.

[0087] MAPA ionic liquid and dimethyl sulfoxide (DMSO) were mixed evenly and then spin-coated onto the electron transport layer. The spin-coating speed was set to 3000 rpm / min and the time was 40 s to obtain the interface modification layer. The concentration of the MAPA ionic liquid after mixing evenly was 0.01 mmol / mL-1 mmol / mL.

[0088] In some other embodiments, the MAPA ionic liquid can also be mixed with DMSO, DMF or anhydrous ethanol, n-butanol, etc. to prepare the interface modification layer.

[0089] In this embodiment, a MAPA ion solution with a CAS number of 54856-22-3 from Biolight is mixed with dimethyl sulfoxide for preparation.

[0090] See also Figure 6-Figure 7 , Figure 6 The device efficiency IV curve of perovskite solar cells prepared with different mixing ratios of MAPA. Figure 7 The device efficiency comparison diagram of perovskite solar cells prepared with different mixing ratios of MAPA, specifically the ratio of MAPA ionic liquid to dimethyl sulfoxide 5μL to 1mL, 10μL to 1mL and 20μL to 1mL, is shown in FIG. Figure 6-Figure 7 It can be seen that among the three mixing ratios, when the mixing ratio of MAPA is 10 μL to 1 mL, the efficiency of the perovskite solar cell is the highest and the device efficiency is the most stable. The control device is a device without MAPA ionic liquid.

[0091] In some other embodiments, methylamine propionate (MAPA) may also be replaced by ionic materials containing methylamine functional groups such as methylamine formate and methylamine acetate.

[0092] Step S104: preparing a perovskite light absorption layer on the interface modification layer.

[0093] Specifically, cesium iodide, lead iodide, and cesium bromide are dissolved in a solvent of DMSO and anhydrous ethanol to obtain a perovskite solution, which is then spin-coated on the interface modification layer. The spin coating speed is set to 1500 rpm / min for 15 seconds, and then rotated at 5000 rpm / min for 30 seconds. A two-step annealing method is used, first annealing at 45°C for 1 minute, and then annealing at 250°C for 1 minute to obtain the perovskite light absorption layer.

[0094] Step S105: preparing a hole transport layer on the perovskite light absorption layer.

[0095] Specifically, the polythiophene donor (PDCBT) was dissolved in chlorobenzene (CB) at a concentration of 4 mg / mL and spin-coated onto the titanite light absorption layer. The spin coating speed was set to 1500 rpm / min for 35 s, and then annealed at 85°C for 1 min. MoO3 (10 nm) was evaporated by thermal evaporation to obtain a hole transport layer.

[0096] Step S106: preparing a metal electrode on the hole transport layer.

[0097] Ag (100 nm) was deposited by thermal evaporation to obtain a metal electrode.

[0098] Example 4

[0099] One embodiment of the present application provides a method for preparing a perovskite solar cell, referring to Figure 8 ,include:

[0100] Step S101: preparing a bottom electrode.

[0101] Specifically, the indium tin oxide (ITO) substrate was cleaned with pure water, acetone, and anhydrous ethanol in sequence, and then placed in a drying oven for drying, and then ozone was generated with an ozone machine for 15 minutes to obtain a bottom electrode.

[0102] Step S102: preparing an electron transport layer on the bottom electrode.

[0103] Specifically, zinc oxide ZnO and isopropyl alcohol IPA are evenly mixed in a volume ratio of 1:7 and then spin-coated on the ITO substrate after ozone, i.e., the bottom electrode, and the rotation speed is set to 3000 rpm / min for 30 seconds. After the spin coating is completed, tin oxide (SnO2) and pure water are evenly mixed in a ratio of 1:6.5, and the solution is spin-coated on the zinc oxide (ZnO) layer. The rotation speed is set to 3000 rpm / min for 30 seconds. After the spin coating is completed, it is placed on a hot stage at 150°C for annealing for 10 minutes to obtain an electron transport layer.

[0104] In some other embodiments, zinc oxide ZnO and isopropyl alcohol IPA are uniformly mixed in a volume ratio of 1:3-1:10.

[0105] Step S103: preparing an interface modification layer on the electron transport layer using a MAPA ionic liquid solution.

[0106] MAPA ionic liquid and dimethyl sulfoxide (DMSO) were mixed evenly and then spin-coated onto the electron transport layer. The spin-coating speed was set to 3000 rpm / min and the time was 40 s to obtain the interface modification layer. The concentration of the MAPA ionic liquid after mixing evenly was 0.01 mmol / mL-1 mmol / mL.

[0107] In some other embodiments, the MAPA ionic liquid can also be mixed with DMSO, DMF or anhydrous ethanol, n-butanol, etc. to prepare the interface modification layer.

[0108] In this embodiment, a MAPA ion solution with a CAS number of 54856-22-3 from Biolight is used for preparation.

[0109] In some other embodiments, methylamine propionate (MAPA) may also be replaced by ionic materials containing methylamine functional groups such as methylamine formate and methylamine acetate.

[0110] Step S104: preparing a perovskite light absorption layer on the interface modification layer.

[0111] Specifically, cesium iodide, lead iodide, and cesium bromide are dissolved in a solvent of DMSO and anhydrous ethanol to obtain a perovskite solution, which is then spin-coated on the interface modification layer. The spin coating speed is set to 1500 rpm / min for 15 seconds, and then rotated at 5000 rpm / min for 30 seconds. A two-step annealing method is used, first annealing at 45°C for 1 minute, and then annealing at 250°C for 1 minute to obtain the perovskite light absorption layer.

[0112] Step S105: preparing a connection layer on the perovskite light absorbing layer.

[0113] First, the polythiophene donor (PDCBT) was dissolved in chlorobenzene (CB) at a concentration of 4 mg / mL and spin-coated onto the titanium ore light absorption layer. The spin-coating speed was set to 1500 rpm / min for 35 s, and then annealed at 85 °C for 1 min.

[0114] Then, molybdenum trioxide (10 nm) and gold (Au) were deposited by thermal evaporation, and then a solution of ZnO and isopropyl alcohol (IPA) mixed in a ratio of 1:7 was spin-coated. The spin-coating speed was set to 3000 rpm / min, the time was 30 s, and the surface was annealed at 90 °C after the spin-coating was completed;

[0115] Finally, BCP (3 nm) was deposited by thermal evaporation to obtain a connecting layer.

[0116] Step S106: preparing an organic light absorbing layer on the connecting layer.

[0117] PM6:mbzs-4f was dissolved in chloroform (CF) at a concentration of 7:8.4 mg / mL and 0.5% chloronaphthalene (CN) was added, and then spin-coated on the connecting layer. The spin coating speed was set to 3700 rpm / min and the time was 39 s to obtain an organic light absorbing layer.

[0118] In this embodiment, when the organic light absorbing layer is prepared by spin coating, 18 μL of solution is aspirated each time, and drop coating is performed after the spin coater reaches a specified rotation speed.

[0119] Step S107: preparing a hole transport layer on the organic light absorbing layer;

[0120] MoO3 (10 nm) was deposited by thermal evaporation to obtain a hole transport layer.

[0121] Step S108: preparing a metal electrode on the hole transport layer;

[0122] Ag (100 nm) was deposited by thermal evaporation to obtain a metal electrode.

[0123] Example 5

[0124] One embodiment of the present application provides a perovskite solar cell, which is prepared using the perovskite solar cell preparation method as described above.

[0125] The above description is only a partial embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of disclosure involved in the present application is not limited to the technical solution formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features without departing from the above disclosed concept. For example, the above features are replaced with the technical features with similar functions disclosed in this application (but not limited to) by each other to form a technical solution.

[0126] In addition, although each operation is described in a specific order, this should not be construed as requiring these operations to be performed in the specific order shown or in a sequential order. Under certain circumstances, multitasking and parallel processing may be advantageous. Similarly, although some specific implementation details are included in the above discussion, these should not be construed as limiting the scope of the application. Some features described in the context of a separate embodiment can also be implemented in a single embodiment in combination. On the contrary, the various features described in the context of a single embodiment can also be implemented in multiple embodiments individually or in any suitable sub-combination mode.

[0127] Although the subject matter has been described in language specific to structural features and / or methodological logical actions, it should be understood that the subject matter defined in the appended claims is not necessarily limited to the specific features or actions described above. On the contrary, the specific features and actions described above are merely example forms of implementing the claims.

Claims

1. A perovskite solar cell, characterized in that: It includes a bottom electrode, an electron transport layer, a perovskite light absorption layer, a hole transport layer and a top electrode which are arranged in sequence from bottom to top; wherein an interface modification layer is also arranged between the electron transport layer and the perovskite light absorption layer, and the interface modification layer is prepared from an ionic liquid including a methylamine functional group.

2. The perovskite solar cell according to claim 1, characterized in that At least one connecting layer and an organic light absorbing layer are stacked in sequence between the perovskite light absorbing layer and the hole transport layer.

3. A method for preparing a perovskite solar cell, characterized in that: include: preparing a bottom electrode; preparing an electron transport layer on the bottom electrode; preparing an interface modification layer on the electron transport layer using an ionic liquid including a methylamine functional group; preparing a perovskite light absorbing layer on the interface modification layer; preparing a hole transport layer on the perovskite light absorbing layer; A metal electrode is prepared on the hole transport layer.

4. The method for preparing a perovskite solar cell according to claim 3, characterized in that: The method further comprises: preparing a connecting layer on the perovskite light absorbing layer; An organic light absorbing layer is prepared on the connecting layer.

5. The method for preparing a perovskite solar cell according to claim 3, characterized in that: The specific steps of using an ionic liquid including a methylamine functional group on the electron transport layer to prepare an interface modification layer include: A mixed solution of methylammonium propionate ionic liquid and dimethyl sulfoxide is spin-coated on the electron transport layer to prepare an interface modification layer, wherein the concentration of the methylammonium propionate ionic liquid in the mixed solution of methylammonium propionate ionic liquid and dimethyl sulfoxide is 0.01 mmol / mL-1 mmol / mL.

6. The method for preparing a perovskite solar cell according to claim 3, characterized in that: The specific steps of preparing the electron transport layer on the bottom electrode include: Zinc oxide and isopropyl alcohol are mixed evenly in a volume ratio of 1:3-1:10 and then spin-coated on the bottom electrode to form a zinc oxide layer. After the spin coating is completed, a solution of tin oxide and pure water is mixed evenly in a volume ratio of 1:6.5 and then spin-coated on the zinc oxide layer; After thermal annealing, an electron transport layer is obtained.

7. The method for preparing a perovskite solar cell according to claim 3, characterized in that: The specific steps of preparing the perovskite light absorption layer on the interface modification layer include: Dissolving cesium iodide, lead iodide and cesium bromide in a mixed solvent of DMSO and anhydrous ethanol to obtain a perovskite solution; Spin coating the perovskite solution onto the interface modification layer; After annealing using a two-step annealing method, the perovskite light absorption layer is obtained.

8. The method for preparing a perovskite solar cell according to claim 4, characterized in that: The specific steps of preparing a connection layer on the perovskite light absorbing layer include: The polythiophene donor (PDCBT) was dissolved in chlorobenzene (CB) at a concentration of 4 mg / mL and spin-coated onto the perovskite light absorption layer at a speed of 1500 rpm / min for 35 s, and annealed at 85 °C for 1 min. Molybdenum trioxide and gold were deposited by thermal evaporation, and then ZnO and isopropyl alcohol (IPA) were evenly mixed in a ratio of 1:7 by spin coating. The speed was set to 3000 rpm / min for 30 s, and annealed at 90 °C after spin coating. BCP was deposited by thermal evaporation to obtain a connecting layer.

9. The method for preparing a perovskite solar cell according to claim 3, characterized in that: The specific steps of preparing a hole transport layer on the perovskite light absorption layer include: The polythiophene donor was dissolved in chlorobenzene at a concentration of 4 mg / mL and spin-coated onto the perovskite light absorption layer. The rotation speed was set to 1500 rpm / min for 35 s, and then annealed at 85°C for 1 min. Molybdenum trioxide was then deposited by thermal evaporation to obtain a hole transport layer.

10. A perovskite solar cell, characterized in that: The perovskite solar cell is prepared by the preparation method of any one of claims 3 to 9.